Multicentre study 'rehabilitation of occupational skin diseases –optimization and quality assurance of inpatient management (ROQ)'–results from 12‐month follow‐up. (10th October 2012) - Weisshaar, Elke; Skudlik, Christoph; Scheidt, Reginald; Matterne, Uwe; Wulfhorst, Britta; Schönfeld, Michael; Elsner, Peter; Diepgen, Thomas L.; John, Swen M.; ,
<x xml:space="preserve">Abstract</x> Background. Occupational skin disease (OSD) is common, and imposes a considerable personal and public burden. To tackle OSD, the German stepwise procedure of handling OSD was set up. It contains an interdisciplinary, integrated inpatient rehabilitation measure [tertiary individual prevention (TIP)] [dermatological treatment and diagnostic procedures, and patient education (health and psychological)]. The primary aims of the TIP are reduction of the severity of OSD, reduction in the use of corticosteroids, facilitation of return to work, decreased absence from work, and enhanced quality of life (QoL). It was positively evaluated for a period of 4 weeks after return to work. Objectives. To investigate whether the observed short‐term effects remain significant and meaningful over a period of 12 months after discharge from the TIP. Methods. A prospective design was used to compare clinical and patient‐reported outcome data between admission to a 3‐week inpatient TIP and 12 months after discharge (12‐month follow‐up). Results. Of 1788 individuals admitted to the TIP, data from 1617 individuals were available for analysis. We observed a significant reduction in the severity of OSD, the use of topical corticosteroids, and days of absence from work because of OSD. QoL was significantly improved, and 87.4% were able to return to work and remain in the workforce. Conclusions. A randomized controlled trial would have been desirable, but was not possible, for legal and other reasons. However, the long‐term 12‐month follow‐up shows that the TIP is associated with sustained improvements in terms of ability to work, QoL, and prognosis, and reductions in days of absence from work because of skin conditions and topical corticosteroid application. These results indicate that the TIP provided a reduction in the personal and public burden of OSD.